Pengaruh Citra Merk dan Persepsi Kualitas Produk Terhadap Keputusan Pembelian Produk Mayoutfit Bandung melalui Instagram - Ine Aprianti; Jihan Putri Krismawati (Jurnal Ekonomi Manajemen Perbankan, 2020)
The purpose of this study was to determine the effect of brand image and product quality on purchasing decisions on Mayoutfit Bandung products. The research method used for this research is descriptive verification. The population in this study was Mayoutfit Bandung followers of 1.2 billion, using simple random sampling with a sample size of 100 people.The results of this study indicate that: (1) Descriptive analysis of the Mayoutfit Bandung brand image shows results with good criteria with an average value of 3.53. (2) The results of descriptive analysis regarding the quality of Mayoutfit Bandung products show results with good criteria with an average value of 3.44. (3) The results of descriptive analysis of purchasing decisions show results with good criteria with an average value of 3.52. (4) There is a significant influence between brand image and product quality together on purchasing decisions. Based on the results of the F test, obtained an F count of 40.768. These results indicate that F arithmetic> F table (40.768> 2.36). This can be interpreted that the Effect of Brand Image and Product Quality together affect the Purchasing Decision.